Growing processes, urban sustainability indexes and intervention guidelines in Mar del Plata peri-urban (ARQUISUR Revista, 2012)
A central goal in the debate about urban management is urban sustainability associated with growing processes without prior planning. Mar del Plata has more than 95% of the population of General Pueyrredon County and its growth is associated with “spontaneous” processes. This paper proposes: to analyze the expansion, consolidation and densification processes that shaped Mar del Plata peri-urban between the 1990s and the present; to create indexes for interpreting such processes in terms of urban sustainability; and to contribute strategic guidelines for peri-urban management. To this end, we resorted to prior studies and information, field work and we created a geo-referred base that allowed us to analyze the growing processes. The results indicate that urban expansion was not accompanied by consolidation, and that densification in the last ten years was associated mainly with the growth of poor settlements. The indicators used revealed that growing processes put the peri-urban further away from the expected sustainability conditions, making it necessary to adopt intervention strategies that redirect such processes. Some of these management strategies and alternatives are stated in this paper.
Keywords: sustainable urban development; expansion; consolidation and densification; urban management; urban-rural interface; urbanization